The Continuous and Reversible Transformation of the Polymorphs of an MGAT2 Inhibitor (S-309309) from the Anhydrate to the Hydrate in Response to Relative Humidity - Tetsuya Miyano; Katsuji Sugita; Hiroshi Ueda (MDPI AG, 2024)
Polymorphic control is vital for the quality control of pharmaceutical crystals. Here, we investigated the relationship between the hydrate and anhydrate polymorphs of a monoacylglycerol acyltransferase 2 inhibitor (S-309309). Solvent evaporation and slurry conversion revealed two polymorphs, the hydrate and the solvate. The solvate was transformed into the hydrate by heating. X-ray powder diffraction demonstrated that the hydrate was transformed into an anhydrate via an intermediate state when heated. These crystal forms were confirmed under controlled humidity conditions; the presence of the anhydrate, the intermediate hydrate, or the hydrate depended on the relative humidity at 25 °C. The stoichiometry of S-309309 in water in the hydrate form was 4:1. The hydrates and anhydrates exhibited similar crystal structures and stability. The water of hydration in the intermediate hydrate was 0.1-0.15 mol according to the dynamic vapor sorption profile. The stability and dissolution profile of the anhydrate and hydrate showed no significant change due to similar crystal lattices and quick rehydration of the anhydrate. A mechanism for the reversible crystal transformation between the anhydrate and pseudo-polymorphs of the hydrate was discovered. We concluded that S-309309 causes a pseudo-polymorphic transformation; however, this is not a critical issue for pharmaceutical use.